Results of the Treatment and Evaluation of Quality of Life in Patients with High-Grade Cerebral Arteriovenous Malformations after Endovascular Embolization - Shchehlov, Dmytro V.; Svyrydiuk, Oleh Ye.; Vyval, Mykola B.; Chebanyuk, Svitlana V.; Altman, Igor V.; Mamonova, Maryna Yu. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Treatment options for cerebral arteriovenous malformations (cAVMs) may include radiosurgery, endovascular embolization, microsurgical removal, or a combination thereof. However, treatment of high-grade (Spetzler–Martin grades IV and V) cAVMs remains extremely challenging when aiming complete occlusion. The aim. To study the safety of the endovascular embolization in patients with high-grade cAVMs and its impact on the quality of life (QoL). Materials and methods. Between 2012 and 2022, 174 patients with cAVMs were endovascularly treated at Research and Practical Center for Endovascular Neuroradiology of the National Academy of Medical Sciences of Ukraine with an average follow-up of more than 9 months. Of these patients, 11 (6.3%) and 6 (3.4%) had Spetzler–Martin grade IV and grade V cAVM, respectively. Outcomes after surgical procedures were assessed and QoL was evaluated using standardized EQ-5D-3L questionnaire. Results. Five (29.4%) patients had intracerebral hemorrhage, 6 (35.3%) had seizures, 5 (29.4%) had other non-hemorrhagic manifestations and 1 (5.9%) patient had a neurological deficit as a result of cerebral steal. In 17 patients, 28 embolization sessions were performed, and in nearly all of them (96%) N-butyl cyanoacrylate was used as the preferred embolic agent. There were no procedural complications. After embolization, three (17.6%) patients had neurologic deterioration (temporary in 2 patients and persistent in 1 patient). All the patients were alive at the nearest follow-up. After embolization, 2 (11.7%) patients had recurrent hemorrhage, but without additional morbidity. Two of the five patients after cAVM rupture had some degree of disability. With regard to non-hemorrhagic debut, 8 (72%) patients reported symptom reduction. QoL assessment with EQ-5D-3L questionnaire revealed that severe problems were present in 2 (33.3%) of 6 patients after intracerebral hemorrhage and 2 (18.2%) of 11 patients with non-hemorrhagic manifestation. The mean Visual Analogue Scale score for the hemorrhagic group was 76.4 ± 15 points, while the non-hemorrhagic group’s score was 85.2 ± 14 points. Conclusions. Endovascular embolization, which aims to occlude the bleeding site or improve cerebral steal with a manageable consequence profile, can be used safely in carefully selected patients with high-grade cAVMs. Our experience shows that QoL can be satisfactory in 3/4 of patients after high-grade cAVM embolization, and more data from real-world practice are highly needed to determine the best method and time for improving patient outcomes.